Reasoning web semantic technologies for the web of data : 7th international summer school 2011, Galway, Ireland, August 23-27, 2011 : tutorial lectures - Polleres, Axel (Lecture notes in computer science, 2011)
The Semantic Web aims at enriching the existing Web with meta-data and processing methods so as to provide web-based systems with advanced capabilities, in particular with context awareness and decision support. The objective of this book is to provide a coherent introduction to semantic web methods and research issues with a particular emphasis on reasoning. The 2011 school programme focused around the central topic of applications of reasoning for the emerging Web of Data with twelve exciting lectures. The chapters in the present book provide educational material and references for further reading. The excellent overview articles provided by the lecturers not only serve as accompanying material for the students of the summer school itself: we are happy to present a volume that also provides the general reader an entry point to various topics related to reasoning over web data.